Comparative transcriptomic analyses of two sugarcane Saccharum L. cultivars differing in drought tolerance - Li, Haibi; Gui, Yiyun; Zhu, Kai; Wei, Jinju; Zhang, Ronghua; Yang, Rongzhong; Tang, Liqiu; Zhou, Hui; Liu, Xihui (Frontiers in Plant Science, 2023)
Sugarcane (Saccharum spp.) is an important cash crop, and drought is an important factors limiting its yield. To study the drought resistance mechanism of sugarcane, the transcriptomes of two sugarcane varieties with different levels of drought resistance were compared under different water shortage levels. The results showed that the transcriptomes of the two varieties were significantly different. The differentially expressed genes were enriched in starch and sucrose metabolism, linoleic acid metabolism, glycolysis/gluconeogenesis, and glyoxylate and dicarboxylate metabolic pathways. Unique trend genes of the variety with strong drought resistance (F172) were significantly enriched in photosynthesis, mitogen-activated protein kinases signaling pathway, biosynthesis of various plant secondary metabolites, and cyanoamino acid metabolism pathways. Weighted correlation network analysis indicated that the blue4 and plum1 modules correlated with drought conditions, whereas the tan and salmon4 modules correlated with variety. The unique trend genes expressed in F172 and mapped to the blue4 module were enriched in photosynthesis, purine metabolism, starch and sucrose metabolism, beta-alanine metabolism, photosynthesis-antenna proteins, and plant hormone signal transduction pathways. The expression of genes involved in the photosynthesis-antenna protein and photosynthesis pathways decreased in response to water deficit, indicating that reducing photosynthesis might be a means for sugarcane to respond to drought stress. The results of this study provide insights into drought resistance mechanisms in plants, and the related genes and metabolic pathways identified may be helpful for sugarcane breeding in the future.